Aumento de la eficiencia de avance por disparo cambiando el tipo de explosivo de emulsión encartuchada por emulsión a granel en los frentes de avance de sección 3.5mx3.0m - unidad minera San Vicente – Simsa, 2018 - Solorzano Avalos, CÉSAR ALBERTO (2019)
The blasting process is one of the most important in the operational chain of mining, with the role of the explosives that fragment the rock and obtain development and preparation work to reach the new ore zones more quickly. To achieve this, the San Vicente mining unit, located in the central jungle, comes with an explosive "Emulnor" from the brand FAMESA EXPLOSIVOS S.A.C. This is a problem of fracture and failure, the property of confinement is not adequate; Which results in an advance per shot lower than the expected advance. On the other hand, there is another explosive product on the market of the type of EMULFRAG-MS bulk emulsion manufactured by FAMESA EXPLOSIVOS S.A.C. This explosive is an emulsion with energetic components that allow it to obtain a high rate of detonation and detonation pressure, but above all obtain 100% confinement. In the present work, the characteristics and benefits of the use of this new explosive are described, in addition to which a comparison of the use of explosives in the mention: Emulnor and Emulfrag is made. In particular, the advantages of bulk emulsion are highlighted, due to the improvement property of the explosive confinement; Because its use brings with it an improvement in the advance efficiency: while an effective drilling of 3.19 m, with emulsion encartuchada of advance results of 2.95 m and efficiency of 92.7%; With the emulsion and bulk, an advance of 3.03 m and efficiency of 95.1% is obtained. After a series of tests, we obtained an increase in the efficiency of advancement by the shot when realizing the change of the real emulsion type emulsion and bulk in the advance fronts of section 3.5mx3.0m, obtaining an improvement in the indicators of productivity and costs; The same ones that are shown in this investigation.